Assessing the Effects of Government Financial Assistance, Profit Reinvestment, and Credit Risk Management on Long-Term Survival of MSMEs - Nurchayati, Nurchayati (IJBLE Scientific Publications Community Inc., 2025)
This study investigates the impact of government financial assistance, profit reinvestment, and credit risk management on the long-term survival of Micro, Small, and Medium Enterprises (MSMEs). Given the significant role MSMEs play in economic development, understanding the key determinants of their sustainability is critical. Using data collected from MSME owners and managers through structured questionnaires, the research employed Structural Equation Modeling (SEM) with Smart PLS to test the proposed relationships. The findings reveal that all three factors—government financial assistance, profit reinvestment, and credit risk management—positively and significantly influence the long-term survival of MSMEs. Among them, profit reinvestment had the strongest effect, indicating the strategic importance of internal financial planning for sustained growth. The study contributes to the literature by integrating external and internal financial practices as joint predictors of MSME survival and offers practical implications for policymakers and business practitioners. Recommendations include promoting integrated financial support mechanisms and capacity-building programs to improve risk management and reinvestment practices among MSMEs.